Pembentukan Karakter Religius Siswa Melalui Pembelajaran Pendidikan Agama Islam di Sekolah Menengah Kejuruan - Mar'atul Azizah; Safinatul Jariah; Andika Aprilianto (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2023)
In the learning process, the teacher not only transmits knowledge to students, but the teacher must also have the ability to understand students and their various uniqueness in order to be able to help them face their learning difficulties. Religious character development can be formed through PAI learning. As well, learning activities must be carried out properly and optimally so that learning objectives can be achieved. Research objectives: 1: To describe the formation of students through learning Islamic religious education in class X, SMK Mastna Karim Diwek Jombang. 2. To describe the religiousness of students in class X at SMK Mastna Karim Diwek Jombang, 3. To describe the supporting and guiding factors in the formation of student character through learning Islamic religion in class X at SMK Mastna Karim Diwek Jombang. The research method used by researchers is a qualitative method with a qualitative descriptive design. Data collection techniques included interviews, observation, and documentation. The results of the study: 1. The formation of religious character at SMK Matsna Karim Diwek Jombang goes through three stages, namely, implementation planning and evaluation. 2. The religious character of students at SMK Matsna Karim Diwek Jombang, namely: familiarizing students to pray before and after doing work; celebrating religious holidays such as Mawlid Nabi, Israj Miraj, Living in harmony with adherents of other religions when students are accustomed to religious subjects and respect each other's religious subjects 3. Supporting and inhibiting factors in the formation of religious character at SMK Matsna Karim Diwek Jombang The supporting factors are teachers and parents; the inhibiting factor is the lack of facilities.